Brief Discussion on Characteristic TCM Therapies for Constipation in the Elderly - Xu, Ruihan; Yang, Mingli (Journal of Contemporary Medical Practice, 2025)
Constipation, one of the most common health issues in modern society, has a high prevalence rate, particularly among elderly patients. Although not life-threatening on its own, it significantly impacts quality of life. Clinically, most constipation patients also suffer from other underlying conditions, leading to severely compromised well-being. Therefore, finding effective treatments is crucial for these individuals. Various therapeutic approaches exist for constipation in clinical practice. This article focuses on the characteristic methods of Traditional Chinese Medicine (TCM) and their efficacy in treatment